Implikasi Putusan Mahkamah Konstitusi Nomor 62/PUU-XXII/2024Terhadap Demokrasi Pemilihan Umum 2029 di Indonesia - Anhari, Falih Rizky; Atikasari, Anggi; Husna, Halishatul; Farhana, Farhana; Kasim, Aksah (Amsir Law Journal, 2026)
The Constitutional Court Decision No. 62/PUU-XXII/2024, which annulled the presidential threshold in Article 222 of Law No. 7 of 2017, marks a crucial shift in Indonesia’s presidential electoral design by removing structural restrictions on citizens’ rights to vote and to be elected. This study analyses the decision’s implications for the quality of democracy in the 2029 presidential election, using a normative legal method with statutory, case, and comparative approaches, and drawing on democratic theory and the principle of popular sovereignty in the 1945 Constitution. The findings show that abolishing the presidential threshold can broaden political participation, diversify representation, and reduce the dominance of large coalitions, yet simultaneously increase the risks of political fragmentation, electoral management complexity, and governmental instability. The article argues that the decision must be followed by regulatory reforms to strengthen party verification, deepen internal party democracy, and ensure transparent and accountable candidacy procedures, so that the post‑threshold electoral system becomes more inclusive and fair while maintaining effective governance.